Effect of ozone oil and non-surgical periodontal treatment in patients with type 2 diabetes. In-vivo and in-vitro studies with fibroblasts and Candida albicans - Raquel Alves do CARMO; Ana Carolina Organista CÖRNER; Eduardo Ferreira MARTINS; Gabriel OUVERNEY; Julio Cesar THURLER JÚNIOR; Bruno Kaufmann ROBBS; Vinicius D’Avila Bitencourt PASCOAL; Elisa ESPOSITO; Luciane Portas CAPELO; Gabriela Alessandra da Cruz Galhardo CAMARGO (Journal of Applied Oral Science)
Abstract Aim To evaluate the clinical effectiveness of ozonated sunflower oil (Oz) as an adjunctive of non-surgical periodontal therapy in patients with type 2 diabetes mellitus (DM2), on fibroblast cell viability and migration and the effectiveness of Oz on a Candida albicans (C. albicans) culture. Methodology In total, 32 sites in 16 DM2 with moderate to advanced periodontal disease with periodontal pocket depths ≥5mm were selected. The treatments were divided into two groups: control, saline solution (SS) as an adjunctive of scaling and root planing (SRP+SS), and test, Oz as an adjunctive of SRP (SRP+Oz). Hematological [fasting glucose level (FGL) and hemoglobin A1c (HbA1c)] and microbiological samples were collected from the participants at baseline and three months after periodontal treatment and the microbiological samples were analyzed by PCR. C. albicans was previously tested by the agar diffusion test. The effect of Oz was tested on cell viability and fibroblast migration. Results The groups showed no statistically significant differences (paired t-test-p>0.05) regarding hematological parameters, FGL (median - baseline 171.41, 3 months 164mg/dL), and HbA1c (baseline 8%, 3 months 7.5%) (Kruskal-Wallis One-Way Nonparametric-p>0.05) after periodontal therapy. The groups showed statistical differences for periodontal parameters between baseline and three months (paired t-test-p<0.05). PCR analysis showed a reduction in the percentage of C. albicans in the SRP+Oz group after three months (McNemar’s test-p=0.002). Cell viability was lower in the high glucose Dulbecco’s modified Eagle’s medium (4500 mg/L) than in low glucose (1000 mg/L) (RM-ANOVA-p<0.0001). The wound healing test showed reduced fibroblast migration (one-way ANOVA with Dunnett’s post-test-p<0.01). Oz showed high C. albicans antifungal inhibition (Kruskal-Wallis test-p=0.0001). Conclusions SRP+Oz effectively reduced C. albicans in-vitro and in-vivo but showed no clinical improvements compared to the control. Cell viability and wound healing of fibroblasts showed no improvements.